Islamic Counseling Approach in Developing Students' Morals at MTs Negeri 1 Ternate - Eka Deviyanti S. Djafar; Munisa Husen; Asriyani M Arifin; Adiyana Adam (Golden Ratio of Social Science and Education, 2026)
This study aims to analyze the implementation and effectiveness of the Islamic counseling approach in fostering students' morals at the State Islamic Junior High School 1 Ternate. The increasingly complex problems of adolescent morals in the digital era demand a holistic and integrative approach, particularly in Islamic schools as Islamic educational institutions. This study used a qualitative approach with descriptive research. The research subjects consisted of the Madrasah Principal, Guidance and Counseling teachers, Islamic Religious Education teachers, and students selected by purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using the Miles, Huberman, and Saldaña model with the stages of data condensation, data presentation, and conclusion drawing. Data validity was ensured through triangulation of sources, techniques, and time, as well as member checking. The results of the study indicate that the implementation of Islamic counseling at MTsN 1 Ternate was carried out systematically through individual counseling services, group counseling, and classical guidance with the methods of muhasabah, advice (mau'izhah), exemplary stories (qashash), habituation (ta'widiyah), role models (uswah hasanah), and a spiritual approach through dhikr and prayer. Islamic counseling has proven effective in increasing students' spiritual awareness, strengthening self-control, improving social interactions, and increasing discipline. Supporting factors include the commitment of madrasah management, the competence of guidance and counseling teachers, and the religious environment of the school. Obstacles included the lack of awareness among some students, the limited number of counselors, and the negative influence of the external environment. This study recommends the addition of competent counselors, increased coordination between stakeholders, the development of systematic and measurable programs, and strengthening religious activities to optimize the development of students' morals.